Pengaruh Model Pembelajaran Kooperatif Tipe Two Stay Two Stray Terhadap Hasil Belajar Matematika Siswa pada Materi Aritmatika Sosial - Herman Firdaus; Laila Hayati; Junaidi Junaidi; Amrullah Amrullah (Pendidikan Matematika FKIP Universitas Mataram, 2022)
This study aims to determine the effect of the cooperative learning model type two stay two stray on the learning outcomes of class VII students at MTs Hadil Ishlah Bilebante. This research was a quasi-experimental study with a post-test only non-equivalent research design group. The population in this study was the entire VII MTs Hadil Ishlah Bilebante for the 2021/2022 academic year. In determining the sample, saturated sampling technique was used, where the sample in this study was class VII Girls as a control class and class VII Boys as an experimental class. The instrument used in this study was a post-test on social arithmetic material. Quantitative data analysis was performed using the t-test. the results of data analysis tcount = 2,988 and ttable = 1,684 so that tcount> ttable then H0 was rejected which indicates that there were differences in student mathematics learning outcomes between classes that receive cooperative learning tiepe two stay two stray and direct learning. This shows that learning with the cooperative model of the type of two stay two stray has an effect on the learning outcomes of class VII students of MTs Hadil Ishlah Bilebante on social arithmetic material